A SITE-BASED CONSERVATION APPROACH TO PROMOTE THE RECOVERY OF BANGGAI CARDINALFISH (Pterapogon kauderni) ENDEMIC POPULATIONS - Abigail Mary Moore; Samliok Ndobe; Jamaluddin Jompa (COJ (Coastal and Ocean Journal), 2017)
The endemic Banggai cardinalfish (Pterapogon kauderni) is an Indonesian conservation priority with Endangered species. The goal of this research was to develop a site-based conservation concept appropriate from a bio-ecological viewpoint, based on the unusual characteristics of this species, in particular: (i) mouthbrooder with direct development, leading to reproductively isolated stocks and fine scale genetic structure; (ii) high level of reliance on habitat, in particular symbiosis with benthic animals providing protective micro-habitat. Methods used include review and analysis of published literature and unpublished data, including an analysis using the Marxan spatial planning software. We suggest several policy options and identify research needs, including: (i) base P. kauderni conservation (protection, rehabilitation and sustainable use) on stocks as the basic management unit; (ii) use data on P. kauderni genetic stocks in the zonation of the proposed Banggai Archipelago marine protected area (MPA); (iii) undertake further research to identify stocks/stock boundaries; (iv) apply the "BCF gardens" concept to fine-scale rebuilding of P. kauderni populations and enabling sustainable use through micro-habitat rehabilitation, with a community-based approach supported by a multi-phase scientific research program. The outputs from this study should support efforts towards sustainable management of the Banggai cardinalfish, particularly in the context of strategies to develop and manage an effective sub-national MPA. Keywords genetic stock; habitat/micro-habitat rehabilitation; community-based conservation; marine protected area; Marxan